2011
DOI: 10.1177/1465116510390062
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of euroscepticism in the Netherlands: 2008 versus 1990

Abstract: With a unique longitudinal data set covering a time-span of 18 years, we test to what extent euroscepticism evolved among the Dutch between 1990 and 2008. We compare Eurosceptic attitudes on the eve of the signing of the Treaty of Maastricht with attitudes after the Dutch 'no' in the referendum on the European Constitution. We find a strong increase in euroscepticism among the Dutch. This change did not develop evenly across the educational strata. We propose to explain these differences through the utilitaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 44 publications
1
39
1
Order By: Relevance
“…This negative relationship between education and euroscepticism has generally been explained by socioeconomic, socio-cultural and political factors (Hooghe and Marks, 2005;Loveless and Rohrschneider, 2008;Lubbers and Jaspers, 2011). The central question of our study is whether the relationship between euroscepticism and education has grown stronger over time in Western Europe.…”
Section: Introductionmentioning
confidence: 93%
“…This negative relationship between education and euroscepticism has generally been explained by socioeconomic, socio-cultural and political factors (Hooghe and Marks, 2005;Loveless and Rohrschneider, 2008;Lubbers and Jaspers, 2011). The central question of our study is whether the relationship between euroscepticism and education has grown stronger over time in Western Europe.…”
Section: Introductionmentioning
confidence: 93%
“…Research has shown that resistance to further European integration is growing in various European countries, and that it is particularly strong in the Netherlands (Lubbers & Scheepers, 2010). In many European countries this issue has been increasingly framed and perceived as a threat to the continuation of national identity (Lubbers & Jaspers, 2011). Eurosceptic politicians and commentators have been warning for the creation of a European super state, in which different national identities would be lost.…”
Section: Studymentioning
confidence: 99%
“…In the Netherlands, attitudes towards the EU have become more negative since the early 1990s and notably at a faster pace than in the other Member States (Huijts and De Graaf, 2007; Lubbers and Scheepers, 2007, 2010). The referendum of 2005 elevated the levels of party conflict over EU integration and increased the issue salience of Europe for voters (see De Vries, 2009, p. 163; Lubbers and Jaspers, 2011, p. 36). The referendum also impacted on the 2006 elections, in which the anti‐Treaty parties gained significantly.…”
Section: The Significance Of 2005mentioning
confidence: 99%
“…These developments in the context of a global economic crisis (with the eurozone in a perilous state) (see Serricchio et al . in this issue) are increasingly putting tremendous strain on the European project as a whole (see Lubbers and Jaspers, 2011, p. 36).…”
Section: Introductionmentioning
confidence: 99%